Réponses

2014-03-02T14:45:18+01:00
1) 

2) Les antécédents de 42 sont les résultats de l'équation 2(x-3) = 42 
                                                                                   2x -6 = 42
                                                                                   2x = 42-6 
                                                                                   2x = 36 
                                                                                   x = 36/2 = 18 

18 est un antécédent de 42 

Calculer g(-2) 

2 ( -2 -3 ) = -10

g (5) = 2 (5-3) = 4